PENGARUH SUPERVISI KEPALA SEKOLAH DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU SD DI KECAMATAN PRINGAPUS KABUPATEN SEMARANG - Nurul Inayati; Noor Miyono; Sumarno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problems in this study are (1) is there an influence of principal supervision on the performance of elementary school teachers in Pringapus District, Semarang Regency?, (2) is there an influence of organizational culture on the performance of elementary school teachers in Pringapus District, Semarang Regency?, (3) is there an influence of principal supervision and organizational culture on the performance of elementary school teachers in Pringapus District, Semarang Regency?. The objectives of this study are: (1) to determine the influence of principal supervision on the performance of elementary school teachers in Pringapus District, Semarang Regency, (2) to determine the influence of organizational culture on the performance of elementary school teachers in Pringapus District, Semarang Regency, (3) to determine the influence of principal supervision and organizational culture on the performance of elementary school teachers in Pringapus District, Semarang Regency. The population of this study was all elementary schools in Pringapus District, Semarang Regency, totaling 211 people, and with a sample of 138 people using the proportional random sampling technique. The data collection method used was the questionnaire method. The data analysis used was descriptive data analysis, prerequisite testing and hypothesis testing. Data analysis using SPSS for Window 26 program. The results of this study are as follows: (1) there is a significant influence of principal supervision on teacher performance stated in the equation Ŷ = 53.746 + 0.542X1 with a correlation strength of 0.500 with a contribution size of 0.250 = 25%, meaning that the magnitude of the influence of variable X1 on Y is 25% and the remaining 75% is influenced by other factors. The first hypothesis is proven, (2) there is a significant influence of organizational culture on performance stated in the equation Ŷ = 55.063 + 0.557X2 with a correlation strength of 0.599 with a contribution size of 0.359 = 35.9%, meaning that the influence of variable X2 on Y is 35.9% and the remaining 64.1% is influenced by other factors. The second hypothesis is proven, (3) there is a significant influence of principal supervision and organizational culture on teacher performance which is stated by the equation Ŷ=46.631+0.176X1+0.452X2 with a contribution of 0.373 or 37.3% this value shows that 37.7% of teacher performance is influenced by principal supervision and organizational culture. The remaining 62.7% is influenced by other variables. Hypothesis 3 is proven. The researcher's suggestion is for teachers to carry out learning planning professionally and systematically for the smoothness and effectiveness of the learning process, so that teacher performance will increase. For principals, they can plan, implement and evaluate supervision objectively and measurably so that teacher performance in learning planning can increase. For the education office, hold a learning innovation workshop to provide new knowledge and skills about more creative and effective teaching methods.